2023
DOI: 10.1097/01.hs9.0000967496.62332.46
|View full text |Cite
|
Sign up to set email alerts
|

S146: Genomic Evolution and Resistance to Pirtobrutinib in Covalent BTK-Inhibitor (Cbtki) Pre-Treated Chronic Lymphocytic Leukemia (Cll) Patients: Results From the Phase I/Ii Bruin Study

Abstract: Background:Pirtobrutinib, a highly selective, non-covalent (reversible) BTKi, demonstrated broad efficacy in patients (pts) with CLL/SLL who were resistant to cBTKi. Mechanisms of resistance to pirtobrutinib have not been systematically analyzed to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This suggests that newer noncovalent BTKi might overcome the resistance observed with covalent BTKi even in the context of super-resistant mutants, pointing to the possibility to re-treat a resistant patient with another BTKi after relapse. In the phase 1/2 BRUIN study, pirtobrutinib allowed the clearance of C481 mutations of ibrutinib resistance while new BTK mutations such as L528W, V416L, A428D, D539G, and Y545N and gatekeeper mutations like T474I/F/L/Y were detected at pirtobrutinib resistance [ 110 ]. Further studies are necessary to determine which noncovalent BTKi resistance mutations are able to circumvent or not, as well as to determine their efficacy across a broader population in first-line settings to guide therapy choice and sequencing.…”
Section: Mechanisms Of Resistance To Target Therapy In Cllmentioning
confidence: 99%
“…This suggests that newer noncovalent BTKi might overcome the resistance observed with covalent BTKi even in the context of super-resistant mutants, pointing to the possibility to re-treat a resistant patient with another BTKi after relapse. In the phase 1/2 BRUIN study, pirtobrutinib allowed the clearance of C481 mutations of ibrutinib resistance while new BTK mutations such as L528W, V416L, A428D, D539G, and Y545N and gatekeeper mutations like T474I/F/L/Y were detected at pirtobrutinib resistance [ 110 ]. Further studies are necessary to determine which noncovalent BTKi resistance mutations are able to circumvent or not, as well as to determine their efficacy across a broader population in first-line settings to guide therapy choice and sequencing.…”
Section: Mechanisms Of Resistance To Target Therapy In Cllmentioning
confidence: 99%
“…Recently Wang et al revealed the occurrence of 5 non-C481 mutations (V416L, A428D, M437R, T474I, and L528W) in patients initially responding to but ultimately relapsing on pirtobrutinib (Figure 3) [84]. These mutations cluster within the kinase domain of BTK [84] and result in sidechain point substitutions that impede the binding of both covalent and non-covalent BTK inhibitors [85,92]. Similar to the earlier described C481F/R/Y mutations, point mutations K430R, V416L, A428D, M437R, and L528W cause steric hindrance and structural clashing, preventing the binding of BTKis but also ATP, causing these mutations to be kinase deficient/dead.…”
Section: Non-covalent Btk Inhibitors In Cll and The Rise Of Non-c481 ...mentioning
confidence: 99%
“…Following the pirtobrutinib treatment, samples from patients who progressed were sequenced again and showed the clearance of C481S/Y/R/F mutations. Instead, new BTK mutations such as L528W, V416L, A428D, D539G, Y545N, and gatekeeper mutations like T474I/F/L/Y were detected (Figure 3) [92]. Future studies are necessary to determine which resistance mutations these ncBTKis can or cannot circumvent and their efficacy across a broader patient population.…”
Section: Non-covalent Btk Inhibitors In Cll and The Rise Of Non-c481 ...mentioning
confidence: 99%